2015
DOI: 10.1088/0268-1242/30/10/105033
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap-engineered GaAsSb alloy nanowires for near-infrared photodetection at 1.31μm

Abstract: Single-nanowire photodetectors have potential applications in integrated optoelectronic devices and systems. Here, bandgap-engineered GaAs 0.26 Sb 0.74 alloy nanowires were synthesized via a chemical vapor deposition method. The synthesized nanowires are single crystals grown along the [111] B direction with length up to 50 μm and diameter ranging from 40 to 500 nm. Photodetectors are built based on these single-alloy nanowires, which show a wide response in the near-infrared region with a high response peak l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 43 publications
2
67
0
Order By: Relevance
“…With the narrowest bandgap among all III-V semiconductors, InSb has the strongest intrinsic spin-orbit interaction, making it an ideal channel material for the Majorana fermions detecting devices [1,3,4,77]. Furthermore, the bandgap can be tuned very effectively by the fabrication of ternary alloys with well-controlled composition [7,8,51]. The controllable synthesis of ternary alloys with tunable bandgaps would broaden the applications of Sb-based III-V semiconductors in infrared photodetector, light emitting diodes and wavelength shifters etc.…”
Section: The Fundamental Properties and Growth Mechanism Of Sb-based mentioning
confidence: 99%
See 2 more Smart Citations
“…With the narrowest bandgap among all III-V semiconductors, InSb has the strongest intrinsic spin-orbit interaction, making it an ideal channel material for the Majorana fermions detecting devices [1,3,4,77]. Furthermore, the bandgap can be tuned very effectively by the fabrication of ternary alloys with well-controlled composition [7,8,51]. The controllable synthesis of ternary alloys with tunable bandgaps would broaden the applications of Sb-based III-V semiconductors in infrared photodetector, light emitting diodes and wavelength shifters etc.…”
Section: The Fundamental Properties and Growth Mechanism Of Sb-based mentioning
confidence: 99%
“…With a tunable bandgap, ternary Sb-based III-V NWs are very suitable to fabricate a wide range of infrared photodetectors [44]. For example, the infrared photodetectors based on GaAsSb NWs showed a broadband response in the near-infrared region with a high response peak located in the optical communication region (1.31 μm), as well as an external quantum efficiency of 1.62×10 5 %, a responsivity of 1.7×10 3 AW −1 and a short response time of 60 ms [51]. On the other hand, owing to the high local electric field for a reverse biased Schottky barrier, photodetectors based on the GaAsSb with self-induced rectifying behavior were obtained by Huh et al They found that the photoresponsivity acquired at reverse bias (−3 V) under an illumination intensity of 20.7 mW cm −2 is around 1463 AW, which is 48 000 times higher than GaAs NW based photodetector and 2500 times higher than GaAs/AlGaAs core-shell NW based photodetector, as shown in figure 10(c) [7].…”
Section: Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all semiconducting NWs, III–V semiconductor NWs are promising candidates for photodetectors because of their high absorption coefficient and wide tunable bandgaps . Photodetectors based on III–V semiconductor NWs have been fabricated in different configurations such as core–shell nanostructures, alloys, and heterostructures . Among all III–V NWs, gallium arsenide (GaAs) NWs have gained immense attention for detection application over recent years because of their high light‐to‐electricity conversion efficiency, moderate direct bandgap (1.42 eV), and high compatibility with Si technology, which in turn make them suitable for various outstanding optoelectronic applications like solar cells, photodetectors, p‐n diodes, and field effect transistors …”
Section: Comparison Of Responsivity Optical Gain and Detectivity Ofmentioning
confidence: 99%
“…Among them, GaAs x Sb 1-x can be obtained by incorporating antimony (Sb) into GaAs, allowing the band gap to be easily adjusted from 0.75 to 1.42 eV [6][7][8][9][10]. The diversity of semiconductor structures had been developed, such as GaAsSb/GaAs single/multiple quantum wells [11,12], GaAsSb-GaInAs/GaAs bilayer quantum wells [13], and GaAsSb nanowires [14][15][16][17]. GaAsSb was recognized as the important material for fabrication highperformance optoelectronic devices, such as laser diodes, photo-detectors and transistors [5,17,18].…”
Section: Introductionmentioning
confidence: 99%